A One-Pot, Transition-Metal-Free Procedure for C–O, C–S, and C–N Bond Formation at the Benzylic Position of Methylarenes - Shimojo, Hiroyuki; Moriyama, Katsuhiko; Togo, Hideo (Synthesis, 2015)
Various methylarenes are treated with 1,3-dibromo-5,5-dimethylhydantoin or N-bromosuccinimide and a catalytic amount of 2,2′-azobis(isobutyronitrile) in acetonitrile, carbon tetrachloride, or methyl tert-butyl ether, and then reacted with benzoic acid, p-toluenethiol, sodium p-toluenesulfinate, aqueous dimethylamine, and succinimide (formed from N-bromosuccinimide) to provide the corresponding arylmethyl benzoates, arylmethyl p-tolyl thioethers, arylmethyl p-tolyl sulfones, N-arylmethyl-N,N-dimethylamines, and N-(arylmethyl)succinimides in good yields, respectively. The reactions involve one-pot, transition-metal-free functionalizations to form C–O, C–S or C–N bonds at the benzylic positions of the methylarenes.
Keywords: methylarenes; C(sp3)–H bond activation; Wohl–Ziegler reaction; 1,3-dibromo-5,5-dimethylhydantoin; N-bromosuccinimide